2015
DOI: 10.12657/folmal.023.024
|View full text |Cite
|
Sign up to set email alerts
|

Species of the genus Mercuria Boeters, 1971 (Caenogastropoda: Truncatelloidea: Hydrobiidae) from the European Mediterranean region, Morocco and Madeira, with descriptions of new species

Abstract: Anatomy and morphology of Mercuria species of the Mediterranean region and Madeira were examined. Four new species of Mercuria, M. rolani n. sp., M. tingitana n. sp., M. bakeri n. sp. and M. targuasensis n. sp., are described based on conchological and anatomical evidence. An identification key and a distribution map of Mercuria of the Mediterranean region and Madeira are also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 7 publications
4
15
0
Order By: Relevance
“…Bursal duct shorter than bursa length. Seminal receptacle fingerlike, with a short duct, joining renal oviduct above the insertion point with bursal duct (based on Glöer et al 2015). Penis strap-like, attached to central area of head.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bursal duct shorter than bursa length. Seminal receptacle fingerlike, with a short duct, joining renal oviduct above the insertion point with bursal duct (based on Glöer et al 2015). Penis strap-like, attached to central area of head.…”
Section: Resultsmentioning
confidence: 99%
“…The gastropod genus Mercuria Boeters, 1971 (Truncatelloidea, Hydrobiidae) is widely distributed in continental aquatic systems of western Mediterranean territories and islands (Giusti 1979, Boeters 1988, Glöer et al 2010, Patzner and Glöer 2013, Boeters and Falkner 2017) and more rarely in those of the Atlantic coasts of North Africa (Glöer et al 2015) and Western Europe (Boeters 1988, Kadolsky 2011, Glöer et al 2015, Boeters and Falkner 2017) and Madeira (Glöer et al 2015). This genus currently comprises 26 species occurring mainly in lowland regions of North Africa (nine species; Glöer et al 2015), continental France (six species; Boeters and Falkner 2017), and the Iberian Peninsula and Balearic Islands (four species, Boeters 1988, Glöer et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Giusti et al (1995) identified this species from Malta and Gozo as P. moussonii (Calcara, 1841). Moreover, they proved that Amnicola melitensis Paladilhe, 1869 belonged to Mercuria Boeters, 1971.…”
Section: Introductionmentioning
confidence: 98%